2021
DOI: 10.3390/microorganisms9112245
|View full text |Cite
|
Sign up to set email alerts
|

Serotypes in Adult Pneumococcal Pneumonia in Spain in the Era of Conjugate Vaccines

Abstract: We studied changes in serotype distribution and antimicrobial susceptibility in adult pneumococcal pneumonia in Spain (2011–2019). Among 895 pneumococci collected (433 bacteremic [BPP] and 462 non-bacteremic [non-BPP]), serotypes 3 (17%), 19A (10%), 8 (6.7%) and 11A (6.7%) were the most frequent. Serotypes 16F, 19A and 24F were associated with old people (≥65) and serotypes 4, 7F, 8, 12F and 19F to young adults. Serotypes 12F, 24F and 1 were significantly more frequent in BPP and serotypes 11A, 23A and 19F in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…However, since 2016 the tax of pneumococcal invasive infection has decreased significantly, which is attributable to the systematic vaccination [ 42 ]. Currently, 97.9% of the target children for antinpneumococcal vaccine receive it, but only 68% of the adults older than 65 years uptake it [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, since 2016 the tax of pneumococcal invasive infection has decreased significantly, which is attributable to the systematic vaccination [ 42 ]. Currently, 97.9% of the target children for antinpneumococcal vaccine receive it, but only 68% of the adults older than 65 years uptake it [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 shows the common susceptibility phenotypes in S. pneumoniae and H. influenzae, the associated resistance mechanism and the inferred prevalence of these phenotypes in Spain [36][37][38][39][40][41][42][43].…”
Section: Arrows Indicate Low (R↓) and High Level (R↑) Resistance Or D...mentioning
confidence: 99%
“…Resistance to macrolides would be close to 25%, with simultaneous resistance to both compounds estimated at around 12%. These isolates are increasing in some serotypes not included in the thirteen-valent pneumococcal conjugate vaccine [ 37 , 38 ]. Surveillance studies conducted in Spain have shown that among oral cephalosporins, cefditoren has a similar behaviour to intravenous third-generation cephalosporins, with higher rates of resistance to cefaclor, cefuroxime and cefixime [ 39 ].…”
Section: - Knowing the Local Resistance Mapmentioning
confidence: 99%
“…However, the phenomenon of serotype replacement has occurred, whereby non-vaccine serotypes (NVSs) have expanded to fill the niche left vacant by VSs [ 12 ]. Typically, NVSs have low invasive potential [ [13] , [14] , [15] ], and the overall incidence of IPD has consistently been lower after the implementation of PCV [ 16 , 17 ]. In addition, serotype replacement remains an issue, as it may relatively negate the effectiveness of PCV due to the emergence of IPD related to NVSs [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%